Diplomats’ Immunity to Foreignness: Socialization, Preparation and Work Environment in Expatriate Adjustment - Kadire Zeynep Sayım (Yönetim ve Organizasyon Araştırmaları Dergisi, 2019)
This paper studies expatriate adjustment of diplomats as a polar case, addressing non-MNE expatriates from Turkey with a three-stage, multi-method research design. We focus on how professional socialization, work environment, and pre-departure preparation influence expatriate adjustment in diplomats. Our study also has developed a series of theoretical models on pre-departure training, international experience, and perceptions of diplomats, and the dimensions of diplomats’ professional socialization based on our multi-stage and multi-method empirical study. In conclusion, we discuss our models’ applicability to similar professional and organizational settings with strong professional norms and high job standardization levels. We also suggest further issues for researchers willing to study different professions and expatriate adjustment.